Working Hours of the World Unite? New International Evidence of Worktime, 1870–1913 - Huberman, Michael (The Journal of Economic History, 2004)
This article constructs new measures of worktime for Europe, North America, and Australia, 1870–1913. Great Britain began with the shortest work year and Belgium the longest. By 1913 certain continental countries approached British worktimes, and, consistent with recent findings on real wages, annual hours in Old and New Worlds had converged. Although globalization did not lead to a race to the bottom of worktimes, there is only partial evidence of a race to the top. National work routines, the outcome of different legal, labor, and political histories, mediated relations between hours and income.